S. aureus Colonization, Biofilm Production, and Phage Susceptibility in Peritoneal Dialysis Patients - Karlis Racenis; Juta Kroica; Dace Rezevska; Lauris Avotins; Edgars Skuditis; Anna Popova; Ilze Puide; Viktorija Kuzema; Aivars Petersons (MDPI AG, 2020)
Peritonitis caused by Staphylococcusaureus is of major importance in peritoneal dialysis (PD) patients due to its great virulence profile and biofilm formation ability. Bacteriophages are a potential tool to treat peritonitis resulting from biofilm-associated infections. We screened S. aureus colonization in 71 PD patients from the nasal cavity, groin, and PD exit-site regions and analyzed clinical outcomes in these patients. We performed biofilm-formation testing of different strains and compared the isolates of one patient to detect phenotypic differences in S. aureus. Phage cocktails were used to detect S. aureus in vitro susceptibility. An adaptation procedure was performed in cases of bacterial resistance. Around 30% of PD patients (n = 21) were found to be S. aureus carriers; from these, a total of 34 S. aureus strains were isolated, of which 61.8% (n = 21) produced a strong biofilm. Phenotypic differences in strain biofilm production were detected in eight patients out of ten. All strains were sensitive to commonly used antibiotics. Broadly positive phage lytic activity (100%) was observed in six cocktails out of seven, and bacterial resistance towards phages was overcome using adaptation. Overall phages showed a promising in vitro effect in biofilm-forming S. aureus strains.